Race, Gender, class, and colonial Nationalism: Railway Development in Newfoundland, 1881–1898 - Korneski, Kurt (Labour / Le Travail, 2008)
Abstract Historians have long noted that policies of “progress” were integral to men and women throughout northern North America in the 19th century. A range of scholars have commented on the centrality of railway technology to these policies. Indeed, they have suggested that, in the 19th century, bourgeois nationalists were swept up in a kind of “railway fever,” and that even though there were detractors, the tenacity of pro-railway elites, and the considerable patronage that huge construction loans and contracts provided them, ensured that these projects triumphed over other possibilities. The Newfoundland case suggests that there is a need for both a slightly revised assessment of elites and their views and goals, and a more nuanced reading of the role of ordinary men and women in the policy-making process. While elites in the colony did view the railway as a means of becoming a “progressive” or “modern nation,” and while they viewed economic prosperity and “enlightenment” as central to modernity and progressiveness, commercial dynamism was only one important component of a more encompassing program. Elites supported the railway because it provided them with a way of living according to standards of Britishness that became important to Newfoundlanders and others in “white” settler dominions, especially after the mid-19th century. Central to “Britishness” as policy makers understood the term, was the idea that “British societies” were those in which men lived according to their “god given manly independence.” A careful analysis of the daily press suggests that many working people took these ideals seriously, and that they saw railway work, and the future employment and other economic opportunities its promoters promised, as a means of living according to them. When opponents of railway development did maneuver themselves into power, they found efforts to change course were met with popular upheaval. Ultimately, it was a broadly based solidarity founded on notions of male entitlement that determined which policies were “feasible.”